Dampak Aktivitas Menghafal Al-Qur'an terhadap Emosional Siswa di SMA Negeri 1 Lamongan - Sufyan, Rahmad Rafif; Rizqi, M. Rizal; Junaidi, Mahbub (AS-SABIQUN, 2025)
The activity of memorizing the Qur’an represents a form of spiritual learning believed to have a positive impact on students’ religiosity, psychological balance, and emotional intelligence. This study aims to examine the influence of Qur’an memorization on the emotional intelligence of students at SMA Negeri 1 Lamongan, particularly in their ability to recognize, manage, and express emotions positively. A quantitative correlational approach was employed, with the sample selected using purposive sampling. Data were collected using two validated scales: the Qur’an memorization habit scale and the emotional intelligence scale. Data analysis was conducted using Pearson correlation via SPSS 27.0 for Windows, based on Daniel Goleman’s theory of emotional intelligence and the concept of spirituality in Islamic education. The results show a positive and significant relationship between Qur’an memorization and emotional intelligence, with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.307. This indicates that tahfizh activity contributes 30.7% to students’ emotional intelligence, while the remaining influence is attributed to other factors. These findings suggest that Qur’an memorization routines play a role in shaping character, inner peace, self-control, emotional stability, and social empathy. The study concludes by emphasizing the importance of integrating tahfizh programs into general education as a strategy for character development and enhancing students’ emotional resilience.